STRATEGI PENGEMBANGAN BANK SAMPAH DI KABUPATEN BARITO TIMUR - Yuchitadewi, Pitaloka; Mahreda, Emmy Sri; Mahyudin, Rizqi Putri; Mirwan, Agus (Universitas Lambung Mangkurat, 2024)
The significant growth in the amount of waste can cause various problems, so management efforts are needed to convert waste into more useful and useful material. Waste banks are facilities used as an alternative to waste management to reduce environmental pollution that will be caused by waste generation. This study aims to analyze the internal and external factors that influence the development of the Mentari Tamiang Layang Waste Bank is in quadrant l, which is in the alternative strategy section. The results of the SWOT matrix showed that there are nine alternatives that can be carried out by the Waste Bank, namely (1) improving Waste Bank services to customers by optimizrng existing facilities, (2) making innovations and increasing creativity to process recycled waste products, (3) marketing products from recycled waste, (4) requiring local government support so that the Waste Bank is more advanced and developed. (5) collaborate with parties that can support the development of the Waste Bank, (6) improve the implementation of larvs and regulations in waste management, (7) increase public awareness in preserving the environment by conducting socialization activities, (8) coordinate with the Regional Government related to the development of the Waste Bank, and (9) maintain bid prices so that cooperation with customers remains well establi shed.